The Construction of Turkey’s Circassians as a Docile Minority - Sunata, Ulaş (Poligrafi, 2021)
The 2014 Sochi Olympic Winter Games revived memories related to the Circassians’ forced migration from their Caucasus homeland into the Ottoman Empire after 150 years. In that year, I conducted a considerable oral history project to understand the collective memories of Circassians in Turkey. The main focus of this study is, however, the social construction of the Circassian minority in Turkey. I examine their oral historical narratives related to their immigration, reception and resettlement, and instrumentalization. It is as important to place emphasis on the protected, multiplied and renewed sociocultural values of Circassians as it is to confront the history. I will examine the relationship between their diasporic identity and minority identity as well as their preferences in identity reproduction.